2016
DOI: 10.1080/08998280.2016.11929380
|View full text |Cite
|
Sign up to set email alerts
|

Delivering Bad News to Patients

Abstract: When physicians lack proper training, breaking bad news can lead to negative consequences for patients, families, and physicians. A questionnaire was used to determine whether a didactic program on delivering bad news was needed at our institution. Results revealed that 91% of respondents perceived delivering bad news as a very important skill, but only 40% felt they had the training to effectively deliver such news. We provide a brief review of different approaches to delivering bad news and advocate for trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(111 citation statements)
references
References 10 publications
5
89
0
17
Order By: Relevance
“…This was consistent with the findings of Bousquet et al's 23 reported to be a source of discomfort for HCPs due to them perceiving a lack of training in this area 28 and having to concurrently manage their own emotional reactions. 23 This review found that patients and family members viewed hav- This variation may be culturally informed, as reflected in models of breaking bad news that have been developed for different cultural settings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was consistent with the findings of Bousquet et al's 23 reported to be a source of discomfort for HCPs due to them perceiving a lack of training in this area 28 and having to concurrently manage their own emotional reactions. 23 This review found that patients and family members viewed hav- This variation may be culturally informed, as reflected in models of breaking bad news that have been developed for different cultural settings.…”
Section: Discussionsupporting
confidence: 90%
“…Given this finding, holistic models of health care that include attending to a patient's psychological wellbeing may apply to the bad news context over and above what a biomedical model of care can offer. However, this may be challenging as managing patients' and family members' emotions has been reported to be a source of discomfort for HCPs due to them perceiving a lack of training in this area and having to concurrently manage their own emotional reactions …”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, difficulty in assisting the family to accept the condition of family members who are critically ill. Delivering information to the patient's family was increasingly difficult especially when the nurse has to deal with a denial patient's family. In accordance with research that conducted by Griffiths (Monden, Gentry, & Cox, 2016) stated that it is not easy to deliver bad news to patients or families. Moreover, sometimes they enter a phase where they cannot accept the situation.…”
Section: Discussionsupporting
confidence: 67%
“…The doctors, nurses and nursing assistants who took part in this study all agree that in developing their professional competence, they learned to communicate with patients by means of trial and error and by imitation, from observing the actions of colleagues with more experience. None of the medical workers taking part in our study had received a refresher course or specific training in this respect, a shortcoming that has also been reported in previous research [32][33][34][35].…”
Section: Discussionmentioning
confidence: 91%